2016
DOI: 10.1021/acs.iecr.6b01635
|View full text |Cite
|
Sign up to set email alerts
|

Screening of Carbon-Supported PdAg Nanoparticles in the Hydrogen Production from Formic Acid

Abstract: A screening of carbon-supported PdAg nanoparticles (NPs) (PdAg/C) in the H 2 production from formic acid (FA) dehydrogenation was carried out by using uniform ~3-5 nm PdAg alloy NPs with a wide compositional range in terms of PVP/Metal and Pd/Ag ratios. The evaluation of the catalytic performance combined with the detailed characterization indicated the beneficial effect of the Ag incorporation and also revealed that the best performance achieved by Pd1Ag2/C (PVP/metal = 1) can be ascribed to its optimum compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 76 publications
2
24
0
Order By: Relevance
“…Our research group reported on the screening of carbonsupported PdAg catalysts prepared by loading pre-synthetized PVP-capped nanoparticles on activated carbon (Shirasagi M), in which the composition of the nanoparticles was optimized in terms of Pd/Ag and PVP/metal molar ratios (Navlani-García et al, 2016c).…”
Section: Effect Of the Nanoparticle Compositionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our research group reported on the screening of carbonsupported PdAg catalysts prepared by loading pre-synthetized PVP-capped nanoparticles on activated carbon (Shirasagi M), in which the composition of the nanoparticles was optimized in terms of Pd/Ag and PVP/metal molar ratios (Navlani-García et al, 2016c).…”
Section: Effect Of the Nanoparticle Compositionmentioning
confidence: 99%
“…H 2 generated after 3 h of reaction over PdAg/C catalysts with a various composition of the nanoparticles. Adapted with permission fromNavlani-García et al (2016c). Copyright 2016 American Chemical Society.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Among them, the catalyst synthesised by FA-reduction was the most active (initial TOF of 90 h −1 at 25 • C), what was claimed to be due to the presence of electron-rich abundant Pd atoms on the surface of the nanoparticles as well as to their alloyed state. Our group also reported on the impact Energies 2019, 12, 4027 6 of 27 of the surface Pd/Ag ratio in the final catalytic performance [43]. In that study, we used a promising synthetic strategy based on the preparation of colloidal PVP-capped PdAg nanoparticles through the reduction by solvent method.…”
Section: Carbon-supported Pdag Catalystsmentioning
confidence: 99%
“…The more convenient use of heterogeneous catalysts has motivated the search for new alternatives to achieve competitive and selective heterogeneous systems able to catalyze the dehydrogenation of FA under mild or moderate conditions. Significant breakthroughs in the field have been achieved while exploring aspects such as the features of the metallic active phase [42][43][44][45][46] or the properties of the support [44,[47][48][49][50]. Most of the investigation reported so far use relatively high temperatures to achieve acceptable conversion of FA into H2.…”
Section: Introductionmentioning
confidence: 99%